Recognition of HER2 expression in hepatocellular carcinoma and its significance in postoperative tumor recurrence - Ji‐Hua Shi; Wen‐Zhi Guo; Yang Jin; Hua-Peng Zhang; Chun Pang; Jie Li; Pål‐Dag Line; Shui‐Jun Zhang (Cancer Medicine)
Abstract Background The ERBB2 oncogene hypothesis is challenged in hepatocellular carcinoma (HCC) with the conflicting evidences of human epidermal growth factor receptor 2 (HER2) overexpression. HER2 could be a new target as a treatment option for HCC as well as tumor recurrence after surgery. HER2 in HCC biology needs further explorations. Methods Clinical and mRNA data of HCC patients were obtained from TCGA HCC cohort, GSE89377 and GSE115018. Western Blotting and immunohistochemistry were employed to test expression of HER2, E‐cadherin, and Vimentin. In HepG2, JM1, HER2‐transfected McA cells, and TGF‐β cocultured JM1 cells, HCC biology, including cell survival, proliferation, and epithelial‐to‐mesenchymal transition (EMT) phenotypes were evaluated. Results ERBB2 mRNA amplification was found in HCC datasets, and its expression was downregulated in high grade HCC with a worse overall survival. HER2 overexpression was identified in H4IIE, HepG2, JM1 cells, and 82% (14/17) HCC samples, and tumor stage was correlated with expression of HER2, E‐cadherin, and Vimentin (P < 0.05). Trastuzumab with the high concentrations suppressed proliferation of HER2‐positive hepatoma cells (P < 0.05); in the coculture model to induce EMT of JM1 cells, HER2 expression increased with downregulated E‐cadherin and upregulated Vimentin. Trastuzumab intravenous injection inhibited in vivo tumor size and metastases (P < 0.05). Signal analysis revealed that HER2 functioned through upregulation of β‐catenin and inhibition of SMAD3. Conclusion HER2 expression pattern is linked with tumor stage and overall survival; the transforming function of HER2 is found more relevant through β‐catenin and SMAD3. HER2‐targeted treatment is recommended to suppress the HER2‐mediated tumor growth during postoperative liver regeneration.